Pharmacological therapy in adult congenital heart disease: growing need, yet limited evidence. (21st August 2018) - Brida, Margarita; Diller, Gerhard-Paul; Nashat, Heba; Strozzi, Maja; Milicic, Davor; Baumgartner, Helmut; Gatzoulis, Michael A
Abstract: Congenital heart disease (CHD) is the most common inborn defect. Due to advances in paediatric care, surgical, and catheter procedures the number of adults with CHD has grown remarkably in recent years. Most of these patients, however, have residua from their original operation/s and require life-long care, many of them are subjected to further haemodynamic and electrophysiological interventions during adulthood. While such re-do surgical or catheter interventions together with device therapy and transplantation play a key therapeutic role, increasingly, adults with CHD require drug therapy for late complications namely heart failure (HF), arrhythmias, pulmonary and systemic hypertension, thromboembolic events, etc. Unlike other cardiovascular areas, drug therapy in adult CHD is based on scarce clinical data and remains largely empiric. Consequently, pharmacological therapies are individualized to ameliorate patients' symptoms and/or degree of haemodynamic impairment. Thus far, recommendations have been difficult to make and formalized guidelines on drug therapy are lacking. We review herewith the rationale, limited evidence and knowledge gaps regarding drug therapy in this growing cardiovascular field and discuss pharmacotherapy options in specific conditions namely HF, arrhythmias, thrombosis, pulmonary arterial hypertension, contraception, and pregnancy.